Productive parameters and digestibility of chickens, using cayenne (Hibiscus rosa-sinensis) and probiotic (Lactobacilius acidophilus) plus pectin (Orinoquia, 2021)
The growth in broiler chicken production has been a determining factor regarding Colombia’s economy and a determining factor in promoting the countryside’s economic development. Using probiotics containing lactic acid-producing bacteria in broiler chickens’ diet contributes to intestinal flora integrity and stability, thereby hampering pathogen proliferation which helps prevent diseases and improve productivity. This research was aimed at evaluating broiler chicken nutrient digestibility and production parameters by including cayenne pepper flour (Hibiscus rosa-sinensis, L.) with and without a probiotic (Lactobacillus acidophilus) plus pectin in chicken feed to replace concentrated food. This project was carried out in Villavicencio in Colombia’s Meta department; 90 broilers were fed on broiler starter concentrate for 15 days. T1 treatment consisted ofconcentrate commercial (CC) milled crumble, T2 CC plus 6% cayenne flour (CF) and T3 CC plus 12% CF; these treatments were compared with a probiotic (WP) and without it (WoP) plus pectin (PP). Cayenne pepper green stems and leaves were harvested 60 days after the last pruning for making CF; they were dehydrated for 72 hours at 60oC and then ground. The chickens’ average weight was 675.1±50g; a randomised complete block design (RCBD) was used, along with Tukey’s multiple comparison test for statistical analysis of the resulting data. Excreta were collected over a five-day period for estimating digestibility coefficients (DC). Broiler diets and excreta were analysed regarding dry matter (DM), protein, fibre, fat, non-nitrogenous extract (NNE) and neutral detergent fibre (NDF); % total digestible nutrients (TDN) and protein biological value (BV) were estimated. Production variables such as food consumption rate, weight gain, feed conversion and carcass yield were evaluated. T2 had the highest DM WoP DC (0.91) and DM WP DC (0.93) compared to those for T1 (0.71 DM WoP DC and DM WP DC 0.72) (p
Keywords: efficient microorganism; digestibility; broiler; shrub